Meningkatkan Aktivitas dan Hasil Belajar Matematika Menggunakan Model PBL, SR dan ST - Rini Wardani; Herti Prastitasari (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This research aims to describe teacher activities, analyze student activities and learning outcomes through the use of PBL, SR and ST models in fourth grade elementary school mathematics learning. The design of this research was PTK in 4 meetings at SDN Kelampaian Ilir 2. The results of teacher activities at meetings 1 and 4 increased from a score of 28 to a score of 35, very good criteria, the results of classical student activities at meetings 1 and 4 increased from 60% to 100 %, and student learning outcomes at meetings 1 and 4 increased from 50% to 90% with complete criteria. It is hoped that this research will be useful in learning so that there will be increased activity and learning outcomes in the division arithmetic operation material.